Medial Open Transversus Abdominis Plane (MOTAP) Catheters Reduce Opioid Requirements and Improve Pain Control Following Open Liver Resection: A Multicenter, Blinded, Randomized Controlled Trial. Issue 2 (August 2018) - Karanicolas, Paul Jack; Cleary, Sean; McHardy, Paul; Kiss, Alex; Sawyer, Jason; Behman, Ramy; Ladak, Salima; McCluskey, Stuart A.; Srinivas, Coimbatore; Katz, Joel; Coburn, Natalie; Law, Calvin; et al.
Abstract : Objective: Conventional management of pain following open liver resection involves intravenous, patient-controlled analgesia (IV PCA) or epidural analgesia. The objective of this trial was to assess the efficacy of a regional technique called Medial Open Transversus Abdominis Plane (MOTAP) catheter analgesia compared with IV PCA. Methods: This was a blinded, randomized, controlled parallel-arm trial conducted at 2 high-volume centers. Patients undergoing liver resection through a subcostal incision were enrolled. Using a standardized technique, 2 catheters were placed after resection: one in the plane between internal oblique and transversus abdominis and the other in the posterior rectus sheath. Patients were randomized to receive ropivacaine 0.2% (ROP) or saline (NS) through both catheters for 72 hours. All patients received IV PCA with hydromorphone as part of a multimodality analgesia program. Primary outcome was opioid use over the first 48 hours. Results: One hundred fifty-three patients were included in the analysis (71 ROP, 82 NS). Patients receiving ROP used significantly less opioid than patients with NS at 48 hours (median 39.6 mg morphine-equivalent vs 49.2 mg, P = 0.033) and at 72 hours (median 50.0 vs 66.4 mg, P = 0.046). Pain scores at rest and with coughing were significantly lower at all time points in patients who received ROP ( P = 0.002). Median length of hospital stay was 5 days in patients receiving ROP and 6 days in patients who received NS ( P = 0.035). There was no difference between groups in complications [ROP 20 (28.2%) vs NS 26 (31.7%), P = 0.63]. Conclusion: MOTAP catheter analgesia reduces opioid requirements, pain, and length of hospital stay compared with IV PCA following open liver resection with subcostal incisions.